Методологічні властивості верховенства права в цивільному судочинстві України - Дем’янова, О.; Demyanova, O. (Східноєвропейський національний університет імені Лесі Українки, 2015)
Стаття присвячена дослідженню методологічної ролі доктрини верховенства права у цивільному судочинстві України. Висвітлюються змістовні положення доктрини верховенства права в аспекті значення для праворозуміння та визначення основних понять цивільного процесу. Приділяється увага з’ясуванню методологічного значення верховенства права в контексті систематизації доктринальних положень науки цивільного процесу, визначення пріоритетних напрямків розвитку теорії та практики. The article is devoted to the research of methodological role of the doctrine of the rule of law in civil legal proceedings of Ukraine. Based on the recognition of the rule of law as an imperative of civil legal proceedings and civil procedural law, methodological value of the relevant regulations have been defined in the article. Content statements of the doctrine of the rule of law from the aspect of value for understanding of law and definition of the basic concepts of civil process have been described. It is about the role of the rule of law in synthesizing of the concept of law understanding and its application in judicial activity. The author also emphasizes the role of civil process in legal system which indicates a peculiarity of realization of the rule of law in the civil procedural relations. The attention has been paid to clarification of methodological value of the rule of law in the context of systematization of doctrinal statements of the science of civil process, and to the definition of the priority directions of development of the theory and practice.
Methodological Features of the Rule of Law in Civil Legal Proceedings
Keywords: верховенство права; цивільне судочинство; методологія; прецедент; правосвідомість; rule of law; civil legal proceedings; methodology; precedent